"You've Done Very Well" ("Das haben Sie sehr schön gemacht"): On Courage and Presence of Mind in Spiritual Issues. (2nd October 2017) - Schmohl, Corinna
Abstract : Although it is not unusual to be called ad hoc onto a ward where one is not on regular duty, there are special challenges for the pastoral caregiver. For example, one might not be familiar with the staff or with the medical focus of the unit. This study (on multiple visits over the course of a long day) demonstrates vividly that the reason a chaplain is called may not always match the real need of the patient and/or of the persons who are close to that patient. Questions that seem to have nothing to do with pastoral care may have a spiritual core or may imply suffering from feelings of futility, of spiritual pain and unresolved religious issues that often remain largely ignored in practice, despite the "total pain" concept in palliative care. The courage to address spiritual issues explicitly, for example, by offering a ritual in pastoral care, can be crucial inmaking positive changes possible.